Networks in the Russian Market Economy - Lonkila, Markku (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. This book examines the significance of networks among the firms operative in the contemporary Russian software industry in the St. Petersburg region.